Double pancake versus long chalcogen-chalcogen bonds in six-membered C,N,S-heterocycles - Haberhauer, Gebhard; Gleiter, Rolf (Chemistry - a European journal, 2016)
Abstract The double ?pancake? bonding in the dimers of the six-membered heterocycles 1,3-dithia-2,4,6-triazine (4) and 1,3-dithia-2,4-diazine (16) were investigated by means of high-level quantum chemical calculations (B3LYP and CCSD(T)). It was found that the S?S dimers, 20?a and 27, are not the most stable isomers, but the dimers showing short S?N (21?a) and S?C (25, 28) bonds. An investigation of the 5-phenyl-1,3-dithia-2,4,6-triazine (4?b) yields that the syn dimer with two S?S bonds (2.57?Å) is the most stable one. In this dimer, the phenyl groups are placed on top of each other. The additional dispersion energy of the phenyl rings causes a stabilization of the syn-S?S (C2v-like) isomer. As a result, two weak albeit relevant single S?S bonds (2.57?Å) are predicted. These findings contradict the recently published concept of double ?pancake? bonding in the dimer 4?b2.